KEKUATAN MENGIKAT PERJANJIAN DI BAWAH TANGAN DALAM PEMBIAYAAN BANK SYARIAH - Fidhayanti, Dwi (Fakultas Syariah, 2017)
Deed by hand is prepared by parties in a contract personally, and not in the presence of a notary or other official (eg Camat as Land Acquisition Officer) making it difficult to provide legal certainty. The focus of the study in this study, the arrangement of agreements under the hands of the Bank Syariah financing agreement as well as its binding strength. This study is a normative study by examining the juridical construction of the arrangement of agreements under the hand in the financing agreement of Bank Syariah. Bank Syariah financing agreements in Indonesia are based on the Civil Code. This part of the response to the development of new forms in transactions. Agreements which have strong evidentiary power shall be made in writing / Deed. Deed under the hand set forth in articles 1874 - 1984 Civil Code. As long as the parties commit an act of contract law in accordance with the terms of the validity of the agreement (article 1320 Civil Code), then the agreement has a binding legal force as the principle of pact sunt servanda. In QS. Al-Baqarah: 282 requires the recording in carrying accounts payable (financing). The power of binding a covenant either in the form of an authentic deed or deed under the hands of Islamic law is contained in the Qur’an. Al-Maidah: 1 and QS Al-Isra: 34.